Houses : modern natural, natural modern - Broadhurst, Ron. (New York : Rizzoli International Publications, 2010)
This carefully curated presentation of new and recent houses represents the vanguard of architects creating innovative structures that maintain a sensitive relationship to their natural contexts. Author Ron Broadhurst has selected projects on five continents to demonstrate the inexhaustible potential of the modern house to enter into a dialogue with nature. Featured here are houses that are either composed of natural materials or maintain an engaging relationship to the natural landscape, or both, designed by such exciting contemporary architects as Kengo Kuma, Atelier Bow-Wow, KieranTimberlake, Sean Godsell, and Allied Works Architecture.''With more than 230 exceptional color photographs, the book presents houses that incorporate the cutting edge of environmentally sensitive design, as well as those that radically rethink the use of'traditional' materials such as wood and stone. An authoritative collection, Modern Natural/Natural Modern demonstrates uniquely of-the-moment architecture and offers up a vision of how we will think of the relationship between houses and the natural landscape in the decades to come.'--BOOK JACKET.
Keywords: Architecture, Domestic -- Environmental aspects; Sustainable architecture